Daniel Sennert’s Corpuscularian Reforms to Natural Philosophy - Gabriel Müller (Histories, 2023)
Daniel Sennert (1572–1637), professor of medicine and natural philosophy in Wittenberg, defended a highly unusual philosophical system. This paper examines Sennert’s vision of natural philosophy within the context of the rapidly changing environment of the seventeenth century and relates his philosophical innovations to his methodology. The main result is that Sennert’s postulation of corpuscles with substantial forms, though it takes place within the framework of Aristotelian natural philosophy, directly influences his philosophical view of qualities.